2011
DOI: 10.1183/09031936.00035111
|View full text |Cite
|
Sign up to set email alerts
|

Malacia, inflammation and bronchoalveolar lavage culture in children with persistent respiratory symptoms

Abstract: In children with persistent respiratory symptoms despite regular anti-asthma inhalation treatment, diagnostic investigations to exclude underlying disease are warranted.124 children were prospectively enrolled, and 24-h oesophageal pH measurement and fibreoptic bronchoscopy with bronchoalveolar lavage (BAL) were performed. BAL fluid (BALF) was processed for neutrophil counting and bacterial culture. Inflammation of the respiratory mucosa was assessed.A structural abnormality of the central airways was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
30
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 15 publications
11
30
0
3
Order By: Relevance
“…Like previous authors, we also found tracheobronchomalacia to be a common anatomic finding in this population . The age range for finding of tracheobronchomalacia was similar to previous report .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Like previous authors, we also found tracheobronchomalacia to be a common anatomic finding in this population . The age range for finding of tracheobronchomalacia was similar to previous report .…”
Section: Discussionsupporting
confidence: 91%
“…Results of this study are in concordance with previous studies reporting a high rate of anatomic and inflammatory findings on FB performed in children with persistent or atypical wheezing . The rate of a completely normal examination was very low at <12%, which is in the low range of normal examinations reported by others (6.7‐52%) …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thinner tracheal cartilage, therefore, may be a risk factor for tracheomalacia in the vitamin D-deficient mouse model. In humans, pliable tracheal cartilage is known to adversely affect flow dynamics during lower respiratory tract diseases (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, H. influenzae was the most common organism, found in 28-58% of children [4,31,32,37,42,56], with Streptococcus pneumoniae (13-58%) and Moraxella catarrhalis (17-59%) the two other most frequently detected organisms. These results are similar to findings in PBB (online supplementary table S3.2).…”
Section: Microbiology (Kq3 and Kq4)mentioning
confidence: 99%